The contribution of mass media in the life of the nation and state - Setiawan, Benni (Informasi, 2023)
Magazine Adil has done is proof that mass media has an important role in realizing a good life. One of the manifestations of a good life is independence. Magazine Adil is one of the media that participates in being a reporter towards the independence of the Republic of Indonesia with a variety of news wrapped in Islam rahmatan lil alamin.